Mother's Knowledge of Stunting in Toddlers at the Arrabih Pratama Clinic, Pekanbaru - Widya Juliartri; Kiki Megasari (Institute Of Computer Science (IOCS), 2021)
Stunting (dwarfism) is a condition in which toddlers have less length or height compared to age, chronic nutritional problems caused by insufficient nutritional intake for a long time.The stunting limitation is height for age based on the Z-score equal to or less than -2 SD below the standard mean. The prevalence of stunting under five has increased from 2016, namely 27.5% to 29.6% in 2017, the incidence of stunting in Riau province in 2019 reached 10.9%. The purpose of this study was to describe the knowledge of mothers about stunting in children under five at the Pratama Arrabih clinic, Pekanbaru. This research is a descriptive quantitative study using a cross sectional research design. The research was conducted at the Pratama Arrabih clinic from 27 November to 8 December 2020. The population in this study were all mothers who had babies and toddlers and visited the Arrabih Pekanbaru clinic in 2020.. Based on the results of the research that has been done, it was found that of the 30 respondents, most of them 43.3% (13 people) had less knowledge about stunting. The conclusion of this study is that the knowledge of mothers about stunting in toddlers is still lacking. It is hoped that all health workers will assist the government in expanding the coverage of education about stunting so that the public knows about stunting and for further researchers to be able to conduct research with different methods, variables, different sampling techniques and further investigate what factors affect knowledge. mom about stunting